S. Mrożek : Na pełnym morzu / Kabaret Studentów AMG Sphincter. ([wydawca nieznany], 1967)
Karta przedstawienia. Na druku: trzy ryby. Reżyseria: W. Wrzesiński; wykonawcy: M, Cieszewski, M. Prus, K. Chęciński, L. Ochyl, T. Lewandowski.